Polyphenol content, in vitro bioaccessibility and antioxidant capacity of widely consumed beverages. (11th October 2017) - Baeza, Gema; Sarriá, Beatriz; Bravo, Laura; Mateos, Raquel
Abstract: BACKGROUND: Beverages prepared from antioxidant‐rich plants are sources of polyphenols, the bioactivity of which depends on bioaccessibility in the gastrointestinal tract. This work evaluated the polyphenol content and antioxidant capacity of widely consumed beverages such as chamomile tea, yerba mate, a coffee blend (65% roasted: 35% green), and coffee‐like substitutes such as chicory, malt and a soluble cereal mixture. Additionally, the bioaccessibility of the two beverages with the highest antioxidant capacity was evaluated using an in vitro digestion model. RESULTS: Total phenolic content ranged from 11.15 mg 200 mL −1 in chamomile tea, up to 154.53 mg 200 mL −1 in mate or 215.05 mg 200 mL −1 in the blend. These results correlated with the antioxidant capacity analysed by ferric reducing antioxidant power, oxygen radical scavenging capacity and 2, 2′‐azinobis‐3‐ethylbenzothiazoline‐6‐sulphonic acid methods. Yerba mate and the coffee blend showed an average polyphenol recovery after in vitro gastrointestinal digestion of 57% and 78%, respectively. Although both beverages showed similar phenolic composition, polyphenols in coffee were more stable than in yerba mate. Alkaline pH in the intestinal digestion stage was responsible for the observed reduction in polyphenol stability. CONCLUSION: Regular consumption of the studied beverages provides considerable amounts of antioxidants which are relatively stable after simulated digestion, and thus have the potential to prevent oxidative stress‐related disorders. © 2017 Society of Chemical Industry